The effectiveness of autovaccine therapy for local lesions with Pseudomonas aeruginosa infection (experimental studies) - Dercach, Svitlana; Dyachenko , Valentina; Sklyar , Nadiya; Maryushchenko , Anatoly; Kutsay , Nataly (Annals of Mechnikov's Institute, 2025)
Pseudomonas infection has different clinical forms, different localization and severity of the specific process. Clinical approaches to the treatment of different categories of patients are somewhat different. In septic manifestations of infection, the use of antibiotic therapy is important, in the transition to a chronic process and in local lesions, the use of autovaccine therapy is possible. Technologies for the production of autovaccines were developed by us in previous years based on the use of the latest method of photodynamic inactivation of candidate bacteria. The aim of this study was to study the effectiveness of the use of autovaccine therapy for local wound lesions complicated by Pseudomonas infection. For this, first of all, a model of Pseudomonas infection of local lesions in laboratory animals was developed. To prolong the course of local infection, a solution of calcium chloride was used. After the administration of this drug, 0.2 ml of pseudomonas culture at a dose of 6 LD 50 was injected under the crust into the resulting area. The procedure was repeated after 24-48 hours. For experiments on laboratory animals, two autovaccine administration schemes were used: the first - intraperitoneally (twice 0.5 ml with an interval of 5 days); the second - subcutaneously (three times 0.2 ml with an interval of 3 days). The effectiveness of vaccine therapy was assessed by indicators of clinical manifestation of infection, wound healing time and survival compared with the control untreated group of animals. The experiments were conducted on rats and white outbred mice. Infection of skin wounds was carried out with strains of Pseudomonas aeruginosa freshly isolated from inpatients. The results of the studies showed that in the experimental groups of animals where the autovaccine therapy method was used, the healing process was significantly intensified. Wound healing time in vaccinated animals was reduced by two or more times compared to untreated animals, and the quality of healing of the affected skin area was quite high. At the same time, after 30 days, almost complete healing of the affected area was observed. Conclusions: The obtained results of treatment of experimental animals with specific autovaccines confirmed the effectiveness of such therapy in wound forms of Pseudomonas aeruginosa infection. The tested model, which reproduces the wound form of Pseudomonas aeruginosa infection in the experiment, can be used in further studies of the effectiveness of drugs for general and local treatment, which is especially relevant in war time.